Ukrainian migrants as victims (trends in European victimization) - Туляков, Вячеслав Олексійович; Туляков, В. О.; Туляков, Вячеслав Алексеевич; Tuliakov, Viacheslav O.; Tulyakov, Vyacheslav A. (Chișinău, 2023)
New aggressive war in Europe need to understand how preventing activity should be in a dissonance with developing public and social relations. Therefore, the problem of interrelationships of consequences of war, crime, modern victimology, human rights, and criminal justice highlights the idea to protect victims of crime and abuse of power on individual and collective level. To properly organize it one could show the main trends in Ukrainian primary, secondary and tertiary victimization of Ukrainian people during war in UA Additionally we should defy social control schemes through victimization tendencies` analysis. Special attention is devoted to war and crime interrelationships in context of fragmentation of international criminal law, victims’ reparations, and criminal policy development.

Нова агресивна війна в Європі потребує розуміння того, наскільки превентивна діяльність має дисонувати з розвитком публічних і суспільних відносин. Отже, проблема взаємозв’язку наслідків війни, злочинності, сучасної віктимології, прав людини та кримінального правосуддя висвітлює ідею захисту жертв злочинів та зловживання владою на індивідуальному та колективному рівнях. Щоб належним чином це організувати, слід показати основні тенденції первинної, вторинної та третинної віктимізації українського народу під час війни в Україні. Крім того, ми повинні протистояти схемам соціального контролю через аналіз тенденцій віктимізації. Особлива увага приділяється взаємозв’язкам війни та злочинності в контексті фрагментації міжнародного кримінального права, відшкодування шкоди жертвам та розвитку кримінальної політики.
Tuliakov V. Ukrainian migrants as victims (trends in European victimization) / V. Tuliakov // Conferința științifică internațională „OMUL, CRIMINOLOGIA, ȘTIINȚA”, ediția a II-a (24 martie 2023). - Chișinău, 2023. – P. 169-174.
Keywords: victimization; security; penal law; victim; human rights; war; віктимізація; безпека; кримінальне право; жертва; права людини; війна; Research Subject Categories::LAW/JURISPRUDENCE